Catalytic Hydrotreatment of Humins to Bio‐Oil in Methanol over Supported Metal Catalysts. Issue 20 (25th September 2018) - Cheng, Ziwei; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Valorization of humins, the polymeric byproducts formed during the acid‐catalyzed production of HMF (5‐hydroxymethylfurfural) or furfural, is necessary to improve process economics and make biorefineries viable. We report the one‐step catalytic hydrotreatment of humins in methanol to humin oil containing fully or partially deoxygenated compounds. First, we compare four commercial noble‐metal catalysts (Ru/C, Rh/C, Pt/C, and Pd/C). Aromatic hydrocarbons, phenols, and esters are the main products detected by GC. Rh/C achieves the best GC‐detectable oil yield and 75 % humins conversion in 3 h at 400 °C, 30 bar H2, and a catalyst‐to‐humins mass ratio of 1:10. High H2 pressures and intermediate temperatures, reaction times, and catalyst loadings enhance GC‐detectable oil yields. In contrast, high temperatures and long reaction times enhance gasification. Aromatics and phenols are found at high temperatures and long reaction times, whereas esters are the major species at short reaction times and high catalyst loading. 13 C‐isotopic labeling studies confirm, for the first time, that methanol participates in the alkylation and esterification reactions to form aromatic, phenolic and ester products. The reactivity in isopropanol is also discussed. Abstract : Catalytic biomass valorization : The one‐step catalytic hydrotreatment of humins in methanol to humin oil containing fully or partially deoxygenated compounds is reported. Four commercial noble‐metal catalysts (Ru/C, Rh/C, Pt/C, and Pd/C) are compared and 13 C‐isotopic labeling studies confirm that methanol participates in the alkylation and esterification reactions to form aromatic, phenolic, and ester products.